INFORMATION TECHNOLOGIES IN ENDOCRINOLOGY: ENHANCING DIAGNOSIS, TREATMENT, AND PATIENT MANAGEMENT - Ermatova Dilnozaxon Shuxratovna; Ismanova Arofatxon Abduldulhamidovna (TADQIQOTLAR, 2025)
Abstract. Information technologies (IT) have significantly transformed the field of endocrinology by enhancing diagnostic accuracy, personalizing treatment plans, and improving patient management. The integration of AI, big data, electronic health records (EHRs), and telemedicine has revolutionized the way endocrinologists diagnose and treat endocrine disorders such as diabetes, thyroid diseases, and metabolic disorders. This article explores the role of information technologies in endocrinology, emphasizing their impact on diagnostics, treatment personalization, and remote patient management. It also discusses the challenges and ethical considerations related to data security and AI usage. As IT continues to evolve, its integration into endocrinology is expected to improve patient outcomes and foster more efficient and personalized healthcare.